Design and techno-economic evaluation of a nanogrid system for a small-scale public railway station building in Thailand - Ngaopitakkul, Atthapol; Songsukthawan, Panapong; Bunjongjit, Sulee; Sreewirote, Bancha; Yoomak, Suntiti; Pothisarn, Chaichan (My University, 2025)
In Thailand, numerous small-scale public facilities continue to rely on the electrical grid. The integration of renewable energy sources such as photovoltaic (PV) and wind power offers a sustainable alternative; however, their inherent intermittency necessitates advanced solutions such as nanogrid systems, which enable localized energy generation, storage, and management to enhance reliability and autonomy. This study develops a nanogrid-based energy management system for Hua Takhe train station, Thailand, by integrating photovoltaic (PV) panels, wind turbines, and battery energy storage systems (BESS). Using HOMER Pro, multiple configurations were simulated and evaluated across key financial indicators, including Payback Period (PB), Internal Rate of Return (IRR), Return on Investment (ROI), Net Present Value (NPV), and Levelized Cost of Electricity (LCOE). The analysis framework further incorporates economic feasibility evaluation, sensitivity and scenario analysis, and long-term performance and life cycle evaluation, thereby ensuring that both short-term financial viability and long-term sustainability are comprehensively assessed. Results show that PV-dominant nanogrid systems, particularly at larger scales, represent the most practical and cost-effective pathway for sustainable electrification of public facilities in Thailand. The 30PV Nanogrid achieves the most favorable balance between cost and performance, with a NPV of 23,925 USD, a LCOE of 0.04 USD/kWh, a PB of 7 years, an IRR of 13 %, and a ROI of 215 % under long-term life-cycle evaluation. In comparison, the 15PV Nanogrid proves economically marginal, with NPV falling to –9117 USD, PB extending beyond 20 years, IRR turning negative (–5 %), and ROI declining to –40 %, confirming that small-scale nanogrids cannot offset the costs of ESS and hybrid inverters.
Keywords: Economic feasibility; Energy management; Energy storage; Grid-connected; Nanogrid; Photovoltaic; Sensibility analysis; Stand-alone; Techno-economic; Wind turbine